Complications in practical work with IT Asset Management (ITAM) - Dervishaj, Kristiana (2022)
ITAM should be a critical part of an IT strategy in any organization. By collecting data about the computer systems that make up IT services, ITAM can be utilized as a dynamic apparatus concerning equipment and programming use, purchases, and rearrangements. It also assists associations with dealing with their IT bequests more effectively. Throughout the study and research complications and issues were identified in the thesis. ITAM is a useful tool to use and it benefit the organizational processes and functional part.